AP2/ERF transcription factor GmDREB1 confers drought tolerance in transgenic soybean by interacting with GmERFs - Chen, Kai (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.